Extracellular vesicles from human urine-derived stem cells inhibit glucocorticoid-induced osteonecrosis of the femoral head by transporting and releasing pro-angiogenic DMBT1 and anti-apoptotic TIMP1. (15th July 2020) - Chen, Chun-Yuan; Du, Wei; Rao, Shan-Shan; Tan, Yi-Juan; Hu, Xiong-Ke; Luo, Ming-Jie; Ou, Qi-Feng; Wu, Pan-Feng; Qing, Li-Ming; Cao, Zhe-Ming; Yin, Hao; Yue, Tao; et al.
Abstract: Osteonecrosis of the femoral head (ONFH) frequently occurs after glucocorticoid (GC) treatment. Extracellular vesicles (EVs) are important nano-sized paracrine mediators of intercellular crosstalk. This study aimed to determine whether EVs from human urine-derived stem cells (USC-EVs) could protect against GC-induced ONFH and focused on the impacts of USC-EVs on angiogenesis and apoptosis to explore the mechanism by which USC-EVs attenuated GC-induced ONFH. The results in vivo showed that the intravenous administration of USC-EVs at the early stage of GC exposure could rescue angiogenesis impairment, reduce apoptosis of trabecular bone and marrow cells, prevent trabecular bone destruction and improve bone microarchitecture in the femoral heads of rats. In vitro, USC-EVs reversed the GC-induced suppression of endothelial angiogenesis and activation of apoptosis. Deleted in malignant brain tumors 1 (DMBT1) and tissue inhibitor of metalloproteinases 1 (TIMP1) proteins were enriched in USC-EVs and essential for the USC-EVs-induced pro-angiogenic and anti-apoptotic effects in GC-treated cells, respectively. Knockdown of TIMP1 attenuated the protective effects of USC-EVs against GC-induced ONFH. Our study suggests that USC-EVs are a promising nano-sized agent for the prevention of GC-induced ONFH by delivering pro-angiogenic DMBT1 and anti-apoptotic TIMP1. Statement of Significance: This study demonstrates that the intravenous injection of extracellular vesicles from human urine-derived stem cells (USC-EVs) at the early stage of glucocorticoid (GC) exposure efficiently protects the rats from the GC-induced osteonecrosis of the femoral head (ONFH). Moreover, this study identifies that the promotion of angiogenesis and inhibition of apoptosis by transferring pro-angiogenic DMBT1 and anti-apoptotic TIMP1 proteins contribute importantly to the USC-EVs-induced protective effects against GC-induced ONFH. This study suggests the promising prospect of USC-EVs as a new nano-sized agent for protecting against GC-induced ONFH, and the potential of DMBT1 and TIMP1 as the molecular targets for further augmenting the protective function of USC-EVs. Graphical abstract: Image, graphical abstract